Political Economy and Economic Policy of the Argentin Crisis: Towards Full Dollarization? (2023)
In the article, a general analysis on economic, social, and political aspects is carried out, that in one way or another led Argentina to a situation of permanent crisis in terms of budget gap. The crisis was motivated by the overflow of public spending, fiscal dominance of monetary policy with structural imbalances in the foreign exchange and external sectors. The various public spending policies and the correlated growth of the monetary base that promotes imbalances on the external front with permanent inflation and devaluation of the national currency that reduce the real competitiveness of the export base are discussed. The article also examines the various government actions in social policy, public spending and fiscal dominance of monetary policy that permanently reduce purchasing power and condemn the population to suffer higher rates of poverty and marginality. It also analyzes the macroeconomic adjustment programs that could eventually be carried out within the Argentine economy to give way to a dollarization program that could facilitate the transition to a definitive solution of the recurrent crises that affect the nation.